ASSISTIVE TECHNOLOGY IN SPECIAL EDUCATION: RESOURCES TO SUPPORT LITERACY, COMMUNICATION, AND LEARNING DIFFERENCES - Ana-Isabel Ma (Universitat Jaume I. Department of English Studies, 2019)
Reviewed by Ana-Isabel Martínez-Hernández Universitat Jaume I, Spain   Assistive Technology in Special Education by Joan L. Green (2018) delves into technology, i.e. apps, websites and devices, to boost learning in students with special needs. With the rise of new technologies in the field of education, many students with disabilities are left behind. Thus, this book intends to show how to use those technologies to make learning easier for physically and mentally challenged students to help them overcome learning difficulties and improve their quality of life. Not only does this book suggest cutting-edge technology, but also everyday gadgets and apps which were not originally created with therapy goals in mind, but end up being so if used correctly, along with state-of-the-art solutions.